Impact of a Carvacrol Treatment on Post-Harvest Ripening Quality and Cell Wall Metabolism in the Kiwifruit - Donglan Luo; Xiaogang Wang; Tingting Mi; Jianye Chen; Liangjie Ba; Sen Cao (Agronomy)
The objective of this study is to investigate the effects of carvacrol on the postharvest storage quality and cell wall metabolism of the ’Guichang’ kiwifruit. For this purpose, the ’Guichang’ kiwifruit is selected as the test material and treated with 0.03 mg/mL of a carvacrol solution for dipping. The storage quality and cell wall metabolism of the fruit are then evaluated under ambient conditions (20 ± 1 °C). The results indicate that treatment with carvacrol effectively reduces the postharvest respiration rate and weight loss in the kiwifruit, while preserving the levels of vitamin C (VC), soluble protein, total phenols, flavonoids, soluble solids, solid–acid ratio, and soluble pectin. Additionally, it delays the decline in the starch content and mitigates the increase in soluble sugars. Furthermore, carvacrol significantly decreases amylase activity and inhibits the elevation of polygalacturonase (PG), pectin methylesterase (PME), β-galactosidase (β-Gal), and cellulase (Cx) activity. Consequently, this treatment effectively maintains fruit firmness as well as protopectin (PP) and cellulose content at elevated levels. A correlation analysis shows that firmness is highly and negatively correlated with the cell wall degrading enzymes PG, PME, β-Gal, Cx, and α-L-Af, with R values of −0.88, −0.83, −0.98, −0.94, and −0.93, respectively. The negative correlation values for the control group are all lower than 0. In conclusion, treatment with carvacrol effectively preserves a high level of postharvest ripening quality in the kiwifruit, attenuates the metabolic processes of the cell wall, and delays fruit softening and senescence.